2021
DOI: 10.1037/sgd0000491
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among LGBTQ cannabis users during the COVID-19 pandemic: Analysis of the COVID-19 cannabis health study.

Abstract: The purpose of this study is to compare the responses of lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) cannabis consumers and their non-LGBTQ counterparts on anxiety, depression, substance use, and coronavirus disease 2019 (COVID-19) coping and stress during the pandemic. Data from an Internet survey of cannabis users during the COVID-19 pandemic were analyzed (N = 2,319). Approximately 18% of the sample identified as LGBTQ. Bivariate analyses were used to examine the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Além disso, é possível identificar questões comuns em todos os países, independentemente do seu nível de desenvolvimento social ou econômico. As preocupações com os altos índices de estresse, depressão e ansiedade ultrapassaram fronteiras, denotando que são problemas mundiais, que ganharam maior visibilidade a partir da pandemia (GATO et al, 2021;GATTAMORTA, et al, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Além disso, é possível identificar questões comuns em todos os países, independentemente do seu nível de desenvolvimento social ou econômico. As preocupações com os altos índices de estresse, depressão e ansiedade ultrapassaram fronteiras, denotando que são problemas mundiais, que ganharam maior visibilidade a partir da pandemia (GATO et al, 2021;GATTAMORTA, et al, 2021).…”
Section: Discussionunclassified
“…Já os europeus mais jovens e que não trabalhavam apresentaram maiores níveis de depressão e ansiedade (GATO et al, 2021). Em pesquisa comparativa, não geolocalizada, do uso medicinal de maconha entre os indivíduos heterossexuais cisgêneros e o grupo LGBTQIA+, identificou-se maior sofrimento psíquico e sintomas de ansiedade e depressão no segundo grupo, acarretando maior consumo de maconha (GATTAMORTA, et al, 2021).…”
Section: Sintomas Psiquiátricos Sofrimento Psíquico E Uso De Substânc...unclassified
“…Data on smoking during the pandemic among LGBTQI + individuals are limited; however, the few that have been published indicated that LGBTQI + individuals were smoking to help alleviate the stress and anxiety they were feeling because of the pandemic [26]. Studies show that LGBTQI + individuals have exhibited increased depressive symptoms and increased use of substances such as alcohol [27,28]. Transgender individuals were particularly affected concerning difficulties in accessing healthcare services related to hormone interventions and gender-affirming surgeries, homelessness, and living with family members who are discriminatory towards their gender identity and/or sexual orientation [29].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with their heterosexual counterparts, SMW have demonstrated poorer health behaviors, including worse nutritional quality, overeating, and stress eating from the beginning of COVID-19. 33 , 34 Substance use behaviors have also disproportionately increased among SMW, including increased use of cannabis and alcohol to cope with COVID-19 related depression and anxiety. 33 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Substance use behaviors have also disproportionately increased among SMW, including increased use of cannabis and alcohol to cope with COVID-19 related depression and anxiety. 33 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%